Child maltreatment and mental health problems in 30-year-old adults: A birth cohort study. (October 2020) - Kisely, Steve; Strathearn, Lane; Najman, Jake Moses
Abstract: Retrospective studies have shown a high association between child abuse and subsequent psychiatric morbidity. Prospective studies are rarer with limited data at 30-year follow-up. This was a prospective record-linkage analysis to examine whether notified and/or substantiated child maltreatment was associated with adverse psychological outcomes in early adulthood when participants were 30 years old. We used data from 2861 young adults who completed the 30-year follow-up phase of the Mater-University of Queensland Study of Pregnancy and its Outcomes, a prospective study commenced in 1981. Exposure to suspected child maltreatment was measured by linkage with state child protection data. The primary outcomes were DSM-IV diagnoses derived from the Composite International Diagnostic Interview-Auto version (CIDI). There were child abuse notifications on 171 participants, of which 103 were substantiated. The most common notifications were for physical abuse (n=96) followed by emotional abuse and neglect (n=80 each). There were 63 notifications of sexual abuse. Of those completing the CIDI at follow-up, 257 participants (9%) reported a depressive disorder, 703 (25%) an anxiety disorder and 138 (5%) PTSD. After adjustment for potential confounders, there were variations in the long-term effects of different types of abuse with physical abuse having a stronger association with depression, and sexual abuse with PTSD. Both emotional abuse and neglect were associated to varying degrees with depression, anxiety and PTSD. Substantiated abuse or multiple forms of abuse had generally the worst outcomes. Highlights: Child abuse and adult psychiatric morbidity are associated in retrospective studies. Prospective studies are rarer with limited data at 30-year follow-up. We studied prospective agency-notified child abuse and affective symptoms in adults. Affective symptoms were more common in all types of abuse. Physical abuse had a strong association with depression, sexual abuse with PTSD.